Prinsip Pendekatan Proses Manajemen Mutu Terpadu dalam Pendidikan di SMK Negeri 4 Samarinda - Astuti, Novi Dwi; Suryani, Yeni; Anita, Anita; Azainil, Azainil; Komariyah, Laili (Lembaga Yasin AlSys, 2025)
The application of integrated quality management principles (TQM) is vital to ensure that every stage of education, from input, process, to output, meets the established quality standards. SMK Negeri 4 Samarinda is one of the vocational schools in Samarinda city that plays an important role in producing ready-to-use middle-level workforce. This study aims to identify the strengths and weaknesses in the implementation of TQM principles and provide strategic recommendations to assist the school in improving its management system comprehensively. This research employs a descriptive qualitative approach with the aim of understanding and deeply describing the application of the process approach principles in integrated quality management at SMK Negeri 4 Samarinda. The results indicate that the implementation of this principle is still not optimal in various aspects. Teacher involvement in the development of quality programs is dominated by passive participation, with only about 20% of teachers actively engaged. Similarly, the realization of the teaching factory program and industrial practice has not been fully equitable, with only 68% of students gaining experience in the teaching factory and 60% of the practice facilities deemed adequate. These findings reflect the incomplete implementation of the process approach in the planning and execution of quality-based learning activities.